The mathematically gifted pupil in the opinion of primary education teacher. Research report - Skarbek, Karolina (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
The article presents results of research, how teachers perceive mathematically gifted children at the primary school education. The results show that many teachers do not see the marks of mathematical talents in the children. Many of them have a very stereotypical image of a gifted pupil.